ANALISIS SPASIAL POTENSI HUTAN RAKYAT DI KABUPATEN BOGOR - Rahmat Safe'i; M Dedy P Sukmara (Forestry Study Program University Of Mataram, 2019)
In order to support the availability of wood raw material and increase the local economy in Bogor, one of the potential that can be developed is a community forest. Although the data and information about community forest areas not yet clearly. Potential data in community forest can get through a spatial approach using remote sensing and geographic information systems. Spatial analysis of the community forest potential was conducted to determine the distribution, extent and type of community forest cover in the district of Bogor. The main data used is Landsat 8 OLI recording of 2015. Processing and analysis of data in this study include, land cover classification, classification of vegetation index and analysis of overlay. Based on the analysis results, community forest area is about 28.351,4 ha spread over 40 districts of Bogor. The largest community forest cover types is a type of agroforestry, and the smallest type of polyculture is the type of monoculture. Based on vegetation index, community forest with a high density is larger than community forest with low density.